Between Organic Visibility and Paid Advertising: Uses of SEO and SEA in Moroccan Tourism SMEs - FAREH, Morad; IDRISSI, Khadija (Revue Internationale des Sciences de Gestion, 2026)
This qualitative study examines the adoption and strategic use of Search Engine Optimization (SEO) and Search Engine Advertising (SEA) among small and medium-sized enterprises (SMEs) in Morocco’s tourism sector. Through semi-structured interviews with 15 tourism SME managers and digital marketing practitioners, complemented by website audits and document analysis, this research explores how Moroccan tourism businesses navigate the choice between organic visibility strategies and paid advertising approaches. Findings reveal that while SEO is perceived as more sustainable and cost-effective, resource constraints, technical knowledge gaps, and competitive pressures drive many SMEs toward SEA solutions. The study identifies a hybrid adoption pattern where businesses combine limited SEO efforts with tactical SEA campaigns, particularly during peak tourist seasons. Results indicate that organizational capabilities, perceived complexity, and institutional pressures significantly influence strategic choices. This research contributes to understanding digital marketing adoption in developing country contexts and provides practical insights for tourism SMEs balancing visibility investments. The study concludes with recommendations for capacity building and strategic framework development tailored to resource-constrained tourism enterprises.